Strategies for functionally graded lattice structures derived using topology optimisation for additive manufacturing - Panesar, Ajit; Abdi, Meisam; Hickman, Duncan; Ashcroft, Ian (Elsevier, 2018)
A number of strategies that enable lattice structures to be derived from Topology Optimisation (TO) results suitable for Additive Manufacturing (AM) are presented. The proposed strategies are evaluated for mechanical performance and assessed for AM specific design related manufacturing considerations. From a manufacturing stand-point, support structure requirement decreases with increased extent of latticing, whereas the design-to-manufacture discrepancies and the processing efforts, both in terms of memory requirements and time, increase.